top button
Flag Notify
    Connect to us
      Facebook Login
      Site Registration Why to Join

    Get Free Puzzle Updates

Facebook Login
Site Registration

If (3!)^2 - (2!)^1 - (1!)^0 - 3! - 2! - 1! - 0! = 7 + x^2 then x^2 - 3x/2 - 4 = ?

0 votes
90 views

If
(3!)^2 - (2!)^1 - (1!)^0 - 3! - 2! - 1! - 0! = 7 + x^2
then
x^2 - 3x/2 - 4 = ?

posted Feb 22, 2017 by anonymous

Share this puzzle
Facebook Share Button Twitter Share Button LinkedIn Share Button

2 Answers

0 votes

6 or 18 Explanation as under
36-2-1-6-2-1-1=7+x^2 or x^2=16 leaving x to be +/- 4
for x^2- 1.5x-4 with x=4 the answer is 16-6-4=6
with x=-4 the answer is 16+6-4=18

answer Feb 22, 2017 by Kewal Panesar
0 votes

Either 6 or -14, since x=±4

answer Mar 25, 2017 by anonymous
Contact Us
+91 9880187415
sales@queryhome.net
support@queryhome.net
#280, 3rd floor, 5th Main
6th Sector, HSR Layout
Bangalore-560102
Karnataka INDIA.
QUERY HOME
...